A study on the atmospheric dispersion of radionuclide released from TRIGA MARK II reactor using gaussian plume model - Jeyleenny Ranty Janson,; Siti Nur Ain Sulaiman,; Suhaimi Kassim,; Nur Syahirah Muszakhir,; Faizal Mohamed,; Syazwani Mohd Fadzil,; Khoo, Kok Siong (Penerbit Universiti Kebangsaan Malaysia, 2019)
TRIGA MARK II reactor is a research facility and site for neutron activation analysis. Should there be fuel rod damage for the first time, amongst its possible causes are human and environmental factor. Consequently, the study objectives were to determine types and released rates of radionuclides dispersed to air and deposited on land through core inventory using ORIGEN2 Code; to determine the concentrations of radionuclides released to air and deposited on land using Gaussian Plume Model; and to determine the exposure doses of radionuclides released to air and deposited on land using exposure dose equation. Core inventory identified types of radionuclides which were Br, I, Kr and Xe. The chosen radioisotopes of Br-83, I-131, Kr-85 and Xe-135 were based on its negative impact on human body system. The maximum released rate of Br-83 was 0.522×105 Bq/s; I-131 was 2.818×105 Bq/s; Kr-85 was 6.447×105 Bq/s and Xe-135 was 4.850×105 Bq/s, respectively. The maximum concentration in the atmosphere for Br-83 was 1.981 Bq/m3; I-131 was 0.062 Bq/m3; Kr-85 was 25.034 Bq/m3 and Xe-135 was 4.248 Bq/m3. The annual exposure doses for four selected radionuclides were 1326 μSv/yr (300 m), 119 μSv/yr (1000 m) and 7.463 μSv/yr (4000 m) for Category B, whereas for Category were 194 μSv/yr (300 m), 17.440 μSv/yr (1000 m) and 1.090 μSv/yr (4000 m), respectively. Conclusively, this study shows that in case of fuel rod damage on TRIGA MARK II reactor, radionuclide atmospheric dispersion at a distance of 300 m (Category B) was exceeding the standard annual exposure dose limit (1000 μSv/yr).